2021
DOI: 10.1002/wer.1569
|View full text |Cite
|
Sign up to set email alerts
|

Modeling transmission of hexavalent chromium concentration and its health cost with a water quality analysis simulation program

Abstract: In this study the Water Quality Analysis Simulation Program (WASP7) was used to evaluate the transmission of hexavalent chromium (Cr(VI)) contamination in a water-sediment system and its flux into cultivated soils. The agricultural areas adjacent to the Wu River in Taiwan were taken as the study area, as these soils were found to be heavily polluted with Cr(VI) concentrations of 3,271-16,799 μg/kg. It was found that the rates of accumulation of Cr(VI) are affected by the distance from the source of 10 −6 in Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(68 reference statements)
0
2
1
Order By: Relevance
“…In Taiwan, the transmission of hexavalent chromium (Cr(VI)) contamination in a water-sediment system and its flux into cultivated soils was used to determine a link to gastric cancer. In this study, highest concentrations of Cr(VI) correlated with greater risk of gastric cancer [31]. However, a systematic review and meta-analysis by Suh et al published a year earlier had concluded that Cr(VI) was not associated with gastric cancer risk [32].…”
Section: Water Sources and Gastric Cancer Riskcontrasting
confidence: 53%
“…In Taiwan, the transmission of hexavalent chromium (Cr(VI)) contamination in a water-sediment system and its flux into cultivated soils was used to determine a link to gastric cancer. In this study, highest concentrations of Cr(VI) correlated with greater risk of gastric cancer [31]. However, a systematic review and meta-analysis by Suh et al published a year earlier had concluded that Cr(VI) was not associated with gastric cancer risk [32].…”
Section: Water Sources and Gastric Cancer Riskcontrasting
confidence: 53%
“…Existing water quality prediction models can be divided into two types: mechanistic and non-mechanistic models [7,8] . Mechanistic models, such as the Streeter Phelps (S-P) model [9][10][11][12] , QUAL2E model [13][14][15] , Water Quality Analysis Simulation Program (WASP) [15][16][17] , Soil and Water Assessment Tool (SWAT) [18][19][20] , etc., are based on physical and chemical principles and require a large amount of basic and long-term monitoring data. However, such data are often unavailable or incomplete in practice, which limits the applicability and accuracy of mechanistic models.…”
Section: Introductionmentioning
confidence: 99%
“…Existing water quality prediction models can be divided into two types: mechanistic and non-mechanistic models [7,8] . Mechanistic models, such as the Streeter Phelps (S-P) model [9][10][11][12] , QUAL2E model [13][14][15] , Water Quality Analysis Simulation Program (WASP) [15][16][17] , Soil and Water Assessment Tool (SWAT) [18][19][20] , etc., are based on physical and chemical principles and require a large amount of basic and long-term monitoring data. However, such data are often unavailable or incomplete in practice, which limits the applicability and accuracy of mechanistic models.…”
Section: Introductionmentioning
confidence: 99%